The effect of unsteadiness on mixed convection boundary-layer stagnation-point flow over a vertical flat surface embedded in a porous medium - Rosali, Haliza; Ishak, Anuar; Nazar, Roslinda; Merkin, John H.; Pop, Ioan (Elsevier, 2014)
The unsteady mixed convection boundary-layer flow towards a stagnation point on a heated vertical surface embedded in a porous medium is considered. The governing partial differential equations are reduced to a system of nonlinear ordinary differential equations using a similarity transformation. These are then solved numerically using the Keller-box method. These numerical results are complemented by asymptotic solutions for large values of A . The influence of dimensionless parameters λλ (mixed convection), A (time variation), n (wall temperature variation) on the flow field and heat transfer is analyzed and discussed, dual solutions being found for both assisting and opposing buoyant flows.